Menanamkan Nilai-Nilai Keimanan Moderat Melalui Pemikiran Al-Asy'ari dan Al-Maturidi dalam Kurikulum Pendidikan Agama Islam - Yanto Maulana Restu; Rika Rahmawati; Ai Elsa Amalia; Lukmanul Hakim (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
This study aims to describe the cultivation of moderate faith values through the theological perspectives of Al-Ashʿarī and Al-Māturīdī within the Islamic Religious Education (PAI) curriculum at MIS Nagarakasih 2 Tasikmalaya. The background of this research is rooted in the challenges of globalization and the diversity of religious interpretations that influence students’ ways of thinking, thereby necessitating a moderate approach in religious education. This study employs a descriptive qualitative method, with data collected through observation and interviews. The findings indicate that moderate faith values such as tasāmuḥ (tolerance), iʿtidāl (justice), tawāzun (balance), and tawassuṭ (the middle path) are integrated into the planning, implementation, and evaluation of Islamic Religious Education learning. PAI teachers play a strategic role in instilling these values through role modeling, habituation of moderate attitudes, and the strengthening of school culture that supports the learning process. The implementation of moderate faith values is supported by a flexible curriculum and institutional support, although challenges remain, particularly those related to students’ individual characteristics. Overall, the theological perspectives of Al-Ashʿarī and Al-Māturīdī remain relevant as a theological foundation for shaping students who possess strong faith, open-minded thinking, and moderate behavior in accordance with the Islamic values of rahmatan lil ʿālamīn.   Keywords: Moderate Faith, Al-Asy'ari, Al-Maturidi, Islamic Religious Education, Religious Moderation.